Unlocking Education Rights: A Path Forward for South Sudan - Kueth, Gatkuoth Simon Duol (Advances in Social Sciences Research Journal, 2025)
This study explores the impact of conflict on access to education in South Sudan, utilising mixed methods to provide a comprehensive analysis. Key findings reveal significant challenges, including insufficient funding for the national Ministry of Education and pronounced inequalities affecting marginalised groups such as girls, children with disabilities, and children from cattle-keeping communities.The research highlights disparities in resource distribution between urban and rural schools, exacerbated by tribal violence. The involvement of local communities, stakeholders, and international agencies is crucial for providing funding and technical support. This study emphasizes the need for policy reform, particularly in areas related to inclusivity and equity. The targeted population includes students in general education, covering both primary and secondary education. Practical implications suggest that improving regional security and increasing international assistance are vital steps towards ensuring equitable access to education for all students in South Sudan.